Pengaruh Pengaruh Kualitas Produk, Brand Ambassador dan Iklan Terhadap Keputusan Pembelian Produk MS Glow - Retna Nur Rahmahyanti; Ana Noor Andriana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to determine the effect of product quality, brand ambassadors, and this advertisement both simultaneously and partially on purchasing decisions on MS Glow products with research locations in Samarinda City. The data analysis technique used was multiple linear regression analysis and the sample in this study was 41 respondents. Sampling was carried out using a saturated sampling technique with the total population used as a sample with the criteria of being domiciled in the city of Samarinda and having purchased MS Glow products. The results of this study partially indicate that the product quality variable has no significant effect on purchasing decisions on MS Glow products. The brand ambassador variable has no significant effect on purchasing decisions for MS Glow products. Advertising variables have a significant effect on purchasing decisions for MS Glow products. Simultaneously product quality, brand ambassadors, and advertising have a significant effect on purchasing decisions for MS Glow products. The test results for the coefficient of determination with a value of 22.9% where the ability of the independent variables in this study, namely product quality, brand ambassadors, and advertisements together can influence the purchasing decision of MS Glow products and the remaining 77.1% can be influenced by other variables not examined in this study.